Financial strategy and tax avoidance: the influence of profit, capital structure, liquidity, and firm size as a moderator - Erdi, Tio Waskito (Journal of Applied Sciences in Accounting, Finance, and Tax, 2025)
The purpose of this study is to examine the effect of profitability, capital structure, and liquidity on tax avoidance, with firm size as a moderating factor. This study was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period, using multiple linear regression techniques and Moderated Regression Analysis (MRA). The results show a significant effect of profitability on tax avoidance, with firms with higher profits more likely to engage in tax avoidance. Conversely, capital structure does not show a significant relationship with tax avoidance, and debt financing is not a dominant tool for reducing corporate tax liabilities. On the other hand, liquidity shows a negative impact on tax avoidance, indicating that more liquid firms are generally more compliant in fulfilling their tax responsibilities. Furthermore, this study confirms that firm size moderates the relationship between the independent variables and tax avoidance, with larger firms being better equipped to implement complex tax strategies due to their sufficient financial and operational capacity. These findings provide valuable insights for corporate decision-makers, policymakers, and investors, emphasizing the importance of maintaining a strategic yet compliant approach to tax planning.